Aminotenuazonic Acid: Isolation, Structure Elucidation, Total Synthesis and Herbicidal Activity of a New Tetramic Acid from Fruiting Bodies of Laccaria Species. Issue 44 (19th July 2019) - Schrey, Hedda; Backenköhler, Jana; Kogler, Herbert; Plaumann, Markus; Spiteller, Peter
Abstract: Invited for the cover of this issue is the group of Peter Spiteller at the Universität Bremen. The image depicts the experiments that were performed to reveal the chemical structure and the bioactivity of aminotenuazonic acid discovered in several Laccaria species, such as the violet‐coloured fruiting bodies of the amethyst deceiver ( Laccaria amethystina ). Read the full text of the article at 10.1002/chem.201901405 . Abstract : "Indeed, fruiting bodies of mushrooms still contain a lot of secrets regarding their natural products." Read more about the story behind the cover in the Cover Profile and about the research itself on page 10333 ff. (DOI: 10.1002/chem.201901405 ).